A qualitative study of informal caregivers' perspectives on the effects of idiopathic pulmonary fibrosis. Issue 1 (3rd January 2014) - Belkin, Amanda; Albright, Karen; Swigris, Jeffrey J
Abstract : Background: Idiopathic pulmonary fibrosis (IPF) is a life-shortening lung disease that leads to significant morbidity in patients. The devastation IPF imposes extends beyond patients: it affects their spouses, loved ones and any other person who might take on the role of informal caregiver (IC) to the patient. Objective: The aim of this study was to capture ICs' perspectives on how they are affected by having a loved one with IPF. Given ICs' vantage, data were also collected on their perceptions of how IPF impacted their patient-loved ones over the course of the disease. Methods: Reflexive team analysis was used to analyse the transcripts from semistructured focus groups conducted with ICs of patients with IPF. Based on the analyses, a conceptual framework of the IC's journey with a patient with IPF was developed and includes suggestions for interventions that might ease the burdens ICs endure while caring for their patient-loved ones. Results: 14 ICs included in this study experienced several hardships throughout the course of their loved ones' illness, from emotional devastation at the time of diagnosis to living with an 'impatient, ' 'cranky' loved one and being forced to exist in a 'smaller world' because of the physical limitations IPF imposed on their partners. The threat of patients needing supplemental oxygen was central to creating angst among patients and ICs, and supplemental oxygen use by patients prohibited them and their ICs from living the 'normal', carefree lives they desired. Conclusions: Being an IC to a patient with IPF is extremely challenging (as 1 IC put it: "…harder on the spouse than the patient in some ways"). As patients attempt to adapt to the 'sick person' role, ICs face a struggle between performing their duties as caregiver and maintaining their own identities and independence.